Detection of fungi from rice black bug Paraeucosmetus pallicornis Dallas (Hemiptera: Lygaeidae) and inhibition with crude extract of Calatropis gigantea (Asclepiadaceae). (May 2018) - Sjam, S; Surapati, U; Adiwena; Syatri, A; Dewi, V S; Rosmana, A
Abstract: Rice black bug ( P. palicornis ) is one of the pests that attack the rice plants in the generative phase that causes the rice easily destroyed when milled and tasted bitter after cooking hence reduces the quality and quantity of rice. The bitter taste in rice may be due to the fungus associated with rice black bug. The aimed of this research was to detect the associated fungi with rice black bug P. pallicornis using some sterilization methods and inhibition with of leaf crude extract of C. gigatea . Detection of fungi from P. pallicornis was conducted using three sterilization methods and control (without sterilization) namely: (1) sterilization with aquades + alcohol 70% (5, 10, 15 and 20 times dipping) + aquades; (2) aquades + alcohol 70% (10 and 20 times dipping); (3) Aquades + alcohol 90 %+ NaCl 0.5 % +alcohol 90 % + aquades. Inhibition of fungi from P. pallicornis with crude extract of C. gigantea obtained by maceration method and then made some concentration to see the effect of its inhibition on the fungi associated with the P. pallicornis . The results showed that without sterilization, four microbe were obtained: Gliocladium sp., Aspergillus sp., black hyphae fungus and white hyphae fungus, sterilization method of Aquades + alcohol 70% with 5 times dipping in alcohol obtained Gliocladium sp., 10 and 20 times dipping found Aspergillus sp. and Gliocladium sp and 15 times dipping found Aspergillus sp. Sterilization with 10 and 20 times dipping in alcohol 70% then washing 2 times with aquades found Gliogladium sp. and Aspergillus sp. Sterilization with Aquades + alcohol 90 % + NaCl 0.5% + alcohol 90% + aquades found Gliocladium sp. Crude extract of C. gigantea had the potential to inhibit fungi Aspergillus sp. and Gliocladium sp. from rice black bug.